Respostas morfogenéticas de bananeira submetida à poliploidização - Costa, Frederico Henrique da Silva (2010)
Most banana cultivars used are triploids and susceptible to important diseases such as black Sigatoka which can lead to 100% of losses. Black Sigatoka control is difficult, costly and unviable to small producers. A viable alternative to overcome this setback is the development of new triploid varieties resistant to this disease and presenting good fruit characteristics. However, conventional breeding has not been very successful in the development of new varieties due to sterility observed in some triploids. Therefore, in vitro polyploidization becomes an important non-conventional genetic breeding strategy. The objectives of the present work are: 1) Develop a new in vitro autotetraploid induction methodology from diploid (AA) Musa acuminata shoot apex; 2) Study the in vitro morphophysiological responses of the shoot apex submitted to colchicine and oryzaline treatments; 3) Develop an efficient and practical technique based on the specific mass of leaf disks of acclimatized plants; 4) Identify, via flow cytometry, putative pre-selected polyploids and correlate to results obtained with the results regarding leaf thickness. The work was carried out at Embrapa located in Cruz das Almas. The following diploids were used: NBA-14, Tong Dog Mak and Malbut. It is concluded that colchicine as well as oryzaline, in adequate concentration and time of exposure, can be used in banana polyploidization. Colchicine presents greater phytotoxicity than oryzaline; however, it promotes greater morphologic variability in regenerated and pre-selected plants as putative polyploids. It is possible to pre-select polyploids by morphologic characteristics. The use of the specific mass of leaf disks enables to distinguish diploids from tetraploids being also useful in the pre-selection of putative polyploids. The polyploid plants identified using the specific mass of leaf disks were confirmed by flow cytometry.